PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH DAN MUDHARABAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Ismawati, Dani; Dailibas, Dailibas; Mubarokah, Isro’iyatul (2021)
With competition between banks and the dominant conventional system, Islamic banks have shown a performance where profitability is above conventional banks. The purpose of this study was to see whether there was any influence between murabahah, musyarakah and mudharabah on profitability. The population of data used comes from the financial statements of Islamic commercial banks listed on the Indonesia Stock Exchange from 2016 to 2019. With the purposive sampling method, 32 data samples were used, but there were 2 outlier data. Therefore the sample data used in the study amounted to 30 data. The research method used is quantitative methods and research techniques with multiple linear regression analysis concluded with a partial test that murabahah has a significant and positive effect on profitability, musharaka has no and negative effect on profitability and mudharabah has no and positive effect on profitability. Then the simultaneous testing concluded that murabahah, musyarakah and mudarabah together affect profitability.